Metabolomic profiling reveals systemic metabolic disruptions induced by combined exposure to particulate matter and ozone - Yue Ge; Maliha S. Nash; Aimen K. Farraj (Current Research in Toxicology)
Air pollution exposure, especially particulate matter (PM) and ozone (O3), poses significant health risks, but the systemic metabolic consequences of combined exposures to PM and O3, remain poorly understood. This study investigated systemic metabolic changes in male spontaneously hypertensive (SH) rats following inhalation exposure to concentrated ambient particles (CAPs) (PM2.5, 150 μg/m3), ozone (O3) (0.2 ppm), and their combination. Rats were exposed for 4 h, and serum samples were collected 1-hour post-exposure. Using targeted metabolomics, we identified significant alterations in metabolites involved in lipid metabolism (phosphatidylcholines), energy metabolism (acylcarnitine C3), and oxidative stress (glutamine). Notably, the combination exposure induced distinct metabolic changes, including increased acylcarnitine C3 levels, suggesting heightened mitochondrial dysfunction. Principal component analysis revealed overlapping profiles between CAPs and controls, indicating a subtler impact of CAPs compared to ozone or combined exposure. These systemic metabolic alterations are aligned with our previously published proteomics findings in cardiac tissues from the same rats, which showed elevated inflammatory markers (e.g., IL-6, TNF-α) and mitochondrial dysfunction. In conclusion, this study provides new insights into the systemic metabolic effects of air pollutant exposure, identifies novel metabolic targets of pollutant-induced toxicity, highlights the complex interactions resulting from combined exposure to multiple pollutants, and underscores the importance of assessing the combined effects of multiple pollutants in air pollution risk assessments.